Analysis of differences in people’s healthy lifestyle during the pandemic and new normal covid-19 in Padang city - Mukhlis Mukhlis; Sari Arlinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is a new type of coronavirus found in humans since the extraordinary events appeared in Wuhan China, in December 2019, later named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2). Healthy lifestyle behaviors can reduce transmission, namely washing hands regularly with soap and water or hand sanitizer, avoiding touching (eyes, nose, or mouth) with hands before washing hands, using masks, avoiding close contact with sick people, enough exercise and enough sleep. The purpose of this research is to describe changes in people's healthy lifestyles during the pandemic and new normal. Method: This type of research is a quantitative study using a cross-sectional design. The study was conducted from January to December 2021. Data processing was carried out by univariate and bivariate analysis through the T-test statistical test. Result: The results of this study showed that 4 healthy lifestyles experienced differences during the pandemic and new normal. A healthy lifestyle is using a mask when outside the house, doing sports regularly, maintaining a minimum distance of 1 meter outside the house and getting enough sleep. Conclusion: The behavior of the community's healthy lifestyle has changed from the pandemic period and the new normal. Abstrak: Latar Belakang: Coronavirus Disease 2019 (COVID-19) merupakan virus corona jenis baru yang ditemukan pada manusia sejak kejadian luar biasa muncul di Wuhan China, pada Desember 2019, kemudian diberi nama Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2). Penularan dapat dikurangi dengan perilaku hidup sehat yaitu rutin mencuci tangan dengan sabun dan air mengalir atau hand sanitizer, menghindari menyentuh (mata, hidung, atau mulut) dengan tangan sebelum mencuci tangan, menggunakan masker, menghindari kontak dekat dengan orang sakit, cukup berolahraga dan cukup tidur. Tujuan dari penelitian ini adalah untuk mendeskripsikan perubahan pola hidup sehat masyarakat pada masa pandemi dan new normal. Metode: Jenis penelitian ini adalah penelitian kuantitatif dengan desain penelitian cross sectional. Penelitian dilakukan pada bulan Januari sampai Desember 2021. Pengolahan data dilakukan dengan analisis univariat dan bivariat melalui uji statistik T-test. Hasil: Hasil penelitian ini menunjukkan ada 4 pola hidup sehat yang mengalami perbedaan saat pandemi dan new normal. Pola hidup sehat adalah menggunakan masker saat berada di luar rumah, rutin berolahraga, menjaga jarak minimal 1 meter saat berada di luar rumah dan tidur yang cukup. Kesimpulan :Perilaku pola hidup sehat masyarakat telah berubah dari masa pandemi dan new normal.